School Size and the Influence of Socioeconomic Status on Student Achievement:Confronting the Threat of Size Bias in National Data Sets - Howley, Craig B.; Howley, Aimee A. (Education Policy Analysis Archives, 2004)
Most of the recent literature on the achievement effects of school size has examined school and district performance. These studies have demonstrated substantial benefits of smaller school and district size in impoverished settings. To date, however, no work has adequately examined the relationship of size and socioeconomic status (SES) with students as the unit of analysis. One study, however, came close (Lee & Smith, 1997), but failed to adjust its analyses or conclusions to the substantial bias toward larger schools evident in the data set used. The present study, based on the same large data set, but with size issues in the rural circumstance clearly in focus, reaches rather different conclusions, extending previous work for the first time to a more adequate examination of size effects on individual students. Findings challenge assertions about ideal and minimum size. Analyses include comparison of means and multi-level modeling. Methodologically, the study illustrates the challenge of using nationally representative data sets of students to investigate second-level contextual phenomena, such as school size. When aggregated to schools attended by nationally representative students, the result cannot be a nationally representative set of schools. Adjustment with weights to simulate such a distribution, moreover, is inadequate to overcome this threat if one is interested in investigating size relationships among the smaller half of US schools, as one must be in seeking to generalize results to the nation as a whole. The present study finds that the smallest national decile of size maximizes the achievement of the poorest quartile of students. Moreover, appropriate size is shown to vary by student socioeconomic status.